1995
DOI: 10.1063/1.114180
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model of element III segregation during molecular beam epitaxy of III-III′-V semiconductor compounds

Abstract: Segregation of column III atoms during molecular beam epitaxy of III-III′-V semiconductor compounds causes nonabrupt interfaces and a surface composition different from the bulk one. To derive concentration profiles, a thermodynamical equilibrium model has been used for a long time. This model applies well to describe segregation processes at high growth temperatures, but fails in predicting concentration profile variations with substrate temperature. We have thus developed a kinetic model which correctly take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
116
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 2 publications
7
116
1
1
Order By: Relevance
“…In accordance with the model proposed by Dehaese et al, [32] at 1.45 ML the average concentration of In in the uppermost layer is certainly greater than 82%. [8] However, our data clearly show that the nucleation is preferential at the step edges, an occurrence which we highlight further.…”
supporting
confidence: 69%
“…In accordance with the model proposed by Dehaese et al, [32] at 1.45 ML the average concentration of In in the uppermost layer is certainly greater than 82%. [8] However, our data clearly show that the nucleation is preferential at the step edges, an occurrence which we highlight further.…”
supporting
confidence: 69%
“…At the same time a more chemically justified model of segregation, initially verified for SiGe alloys, was presented by Fukatsu et al 71 and Fujita et al 72 The same method, known generally as the kinetic model of segregation, was extended to exchanges of group III atoms in III-V alloys by Dehaese et al 73 In the kinetic model of segregation the process of diffusion is assumed to occur only between the growing layer and the one immediately below while all the other layers ͑bulk͒ are considered to be frozen. The evolution of the number of In surface atoms is given by the balance of incoming and leaving In or Ga atoms,…”
Section: Segregation In Epitaxial Layersmentioning
confidence: 99%
“…The previous models of segregation are based on the twostate exchange 70,71,73 mechanism, where only atomic exchange among the subsurface and surface states is considered. Godbey and Ancona 75 instead proposed to extend the kinetic model to a three-layer exchange mechanism.…”
Section: ͑6͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Several models for indium segregation have been proposed. [7][8][9][10] We use the phenomenological model of Muraki et al, 8 which has been shown to describe the indium composition x͑n͒ of InAs WLs well: 3…”
mentioning
confidence: 99%